Progress in optics. Vol. 52 - Wolf, Emil.; Aegerter, Christof M.; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier, 2009)
In the fourty-seven years that have gone by since the first volume of Progress in Optics was published, optics has become one of the most dynamic fields of science. The volumes in this series which have appeared up to now contain more than 300 review articles by distinguished research workers, which have become permanent records for many important developments. - Backscattering and Anderson localization of light - Advances in oliton manipulation in optical lattices - Fundamental quantum noise in optical amplification - Invisibility cloaks.
Coherent backscattering and Anderson localization of light / Christof M. Aegerter and Georg Maret -- Soliton shape and mobility control in optical lattices / Yaroslav V. Kartashov, Victor A. Vysloukh and Lluis Torner -- Signal and quantum noise in optical communications and cryptography / Philippe Gallion, Francisco Mendieta and Shifeng Jiang -- Invisibility cloaking by coordinate transformation / Min Yan, Wei Yan and Min Qiu.
Includes bibliographical references and indexes.
Print version record.
Elsevier
Keywords: Optics; SCIENCE -- Physics -- Optics & Light; Optics; Electronic books